Interference of age and supplementation of direct-fed microbial and essential oil in the activity of digestive enzymes and expression of genes related to transport and digestion of carbohydrates and proteins in the small intestine of broilers - Fernandez-Alarcon, M. F. [UNESP]; Trottier, N.; Steibel, J. P.; Lunedo, R. [UNESP]; Campos, D. M.B. [UNESP]; Santana, A. M. [UNESP]; Pizauro, J. M. [UNESP]; Furlan, R. L. [UNESP]; Furlan, L. R. [UNESP] (Elsevier, 2017)
The objectives of this study were to describe alterations that age and dietary inclusion of direct-fed microbial (DFM) Bacillus subtilis (BS) and a specific essential oil (EO) blend (carvacrol, cinnamaldehyde, cineol, and pepper extract) causes in the activity of digestive enzymes (maltase: MALT; aminopeptidase-N: APN; intestinal alkaline phosphate: IAP) and expression patterns of genes related to transport (oligopeptide transporter gene: SLC15A1; Na+-dependent glucose and galactose transporter gene: SLC5A1; Na+-independent glucose, galactose, and fructose transporter gene: SLC2A2; ATPase, Na+/K+ transporting gene: ATP1A1) and digestion (aminopeptidase-N gene: ANPEP; maltaseglucoamylase gene: MGAM; Sucrase-isomaltase gene: SI) of carbohydrates and proteins in the small intestine of broilers. Also, the objective was to analyze if growth performance of broilers is affected by supplementation (BS and EO blend). Day-old male broiler chicks (n = 1,320) were assigned to 5 treatments. Diets included a basal diet (BD) as a negative control (CON); experimental diets were BD + BS; BD + BS + EO; BD + EO; BD + antibiotic growth promoter (AGP) avilamycin was the positive control. Performance was evaluated between 1 to 42 d. Transcript abundance of transport-related genes and digestion-related genes were assayed by RT-qPCR and determined at d 7, 21, and 42. MALT-, APN-, and IAP-specific activities were determined at d 7, 21, and 42. Broilers fed BS had greater SLC15A1 mRNA abundance compared to CON, while EO and AGP were related to higher activities of IAP and APN. Analysis over time revealed higher abundance of MGAM, SLC2A2, SLC15A1, SLC5A1 and SI mRNA at d 42 when compared to d 7. Activity of IAP decreased after d 7 and activity of MALT increased with age. The current study suggests that age had effect over carbohydrate and protein transport and carbohydrate digestion. The supplementation of BS DFM hade evident effect over protein transport and that the use of EO in the diet enhanced the activities of carbohydrate and protein digestion, reflecting improvement in digestive and transport physiology of birds. Changes performed by BS DFM and EO did not favor performance.
Keywords: Bacillus subtilis; broiler chicken; feed additives; intestine; probiotics